Drug survival rates in patients with psoriasis after treatment with biologics. Issue 12 (4th December 2013) - Umezawa, Yoshinori; Nobeyama, Yoshimasa; Hayashi, Mitsuha; Fukuchi, Osamu; Ito, Toshihiro; Saeki, Hidehisa; Nakagawa, Hidemi
Abstract Clinically, patients' adherence to biologic treatment is not only related to efficacy but also to adverse events, cost and other factors. To evaluate long‐term viability of biologic treatment, both the percentage of and reasons for discontinuation of treatment were investigated. In this study, patients treated with infliximab (n = 38), adalimumab (n = 59) and ustekinumab (n = 30) were included and observed for 12 months. Clinical efficacy was evaluated using a 75% reduction of Psoriasis Area and Severity Index score (PASI‐75), and patients who discontinued treatment were considered as not having achieved PASI‐75. In addition, drug survival rate (DSR) was investigated. In patients treated with infliximab, PASI‐75 was 68.4% and DSR was 73.3% by the end of treatment. In patients treated with adalimumab, PASI‐75 was 50.8% and DSR was 79.7%. In patients treated with ustekinumab, PASI‐75 was 63.3% and DSR was 96.7%. Several patients discontinued treatment because of insufficient efficacy due to secondary failure in infliximab or primary failure in adalimumab. To increase treatment efficacy, it will be necessary for these patients to use an additional concomitant treatment. Higher efficacy is expected with biologics than with conventional treatments; however, the actual clinical efficacy over a long period of time may be insufficient if they are used without any concomitant treatments.